(untitled) (Contemporary Mathematics, 2025)
This paper adopts the direct algebraic method to recover and enlist a full spectrum of optical 1-soliton solutions for the dispersive concatenation model that comes with Kerr law of nonlinear refractive index change. The temporal evolution for the model is taken to be fractional so that the model is viable for controlling the Internet bottleneck-a growing problem in telecommunications industry. The numerical simulations supplement the soliton solutions that are obtained analytically.